Targeted rehabilitation may improve patient flow and outcomes: development and implementation of a novel Proactive Rehabilitation Screening (PReS) service. Issue 1 (8th March 2021) - Wu, Jane; Misa, Olivia; Shiner, Christine T; Faux, Steven G
Abstract : Rehabilitation programmes can be delivered to patients receiving acute care ('in-reach rehabilitation') and/or those who have completed acute care but experience ongoing functional impairments ('subacute rehabilitation'). Access to these programmes depends on a rehabilitation assessment, but there are concerns that referrals for this assessment are often triggered too late in the acute care journey. We describe a Proactive Rehabilitation Screening (PReS) process designed to systematically screen patients during an acute hospital admission, and identify early those who are likely to require specialist rehabilitation assessment and intervention. The process is based on review of patient medical records on day 5 after acute hospital admission, or day 3 after transfer from intensive care to an acute hospital ward. Screening involves brief review of documented care needs, pre-existing and new functional disabilities, the need for allied health interventions and non-medical factors delaying discharge. From May 2017 to February 2019, the novel screening process was implemented as part of a service redesign of the rehabilitation consultation service. Four thousand consecutive screens were performed at the study site. Of those 'ruled in' by screening as needing a rehabilitation assessment, 86.0% went on to receive inpatient rehabilitation interventions. Of those 'ruled out' by screening, 92.1% did not go on to receive a rehabilitation intervention, while 7.9% did receive some form of rehabilitation intervention. Of all patients accepted into a rehabilitation programme (n=516), PReS was able to identify 53.6% (n=282) of them before the acute care teams made a referral (based on traditional criteria). In conclusion, we have designed and implemented a systematic, PReS service in one metropolitan Australian hospital. The process described was found to be time efficient and feasible to implement in an acute hospital setting. Further, it appeared to identify the majority of patients who went on to receive formal inpatient rehabilitation interventions.